2001
DOI: 10.1079/bjn2001397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary oleic-rich oils (virgin olive and high-oleic-acid sunflower) on vascular reactivity in Wistar-Kyoto and spontaneously hypertensive rats

Abstract: The effects of two monounsaturated fatty acid (MUFA)-rich diets, containing virgin olive oil (OO) and high-oleic-acid sunflower oil (HOSO), on development of vascular response from isolated thoracic rat aorta and lipid composition and fatty acid composition were studied and compared with samples from rats fed on a control diet. Dietary MUFA oils were fed for 6 weeks to spontaneously hypertensive (SHR) and Wistar -Kyoto (WKY) rats from 4 weeks of age. The maximum contraction of aortic ring preparations in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
30
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 44 publications
10
30
1
Order By: Relevance
“…Moreover, it has been shown that long-term intake of high doses of olive oil has an inverse association with the risk of developing hypertension (3,4). There has been considerable research effort directed toward analyzing the effects of MUFA-rich diets, focusing on plasma lipids and the lipid/FA composition of cell membranes (5)(6)(7)(8), but the specific molecular mechanisms underlying the beneficial effects of oleic acid and related compounds are still not completely understood.…”
mentioning
confidence: 99%
“…Moreover, it has been shown that long-term intake of high doses of olive oil has an inverse association with the risk of developing hypertension (3,4). There has been considerable research effort directed toward analyzing the effects of MUFA-rich diets, focusing on plasma lipids and the lipid/FA composition of cell membranes (5)(6)(7)(8), but the specific molecular mechanisms underlying the beneficial effects of oleic acid and related compounds are still not completely understood.…”
mentioning
confidence: 99%
“…7 Olive oil consumption causes favorable changes in plasma lipid and lipoprotein profiles 8,9 and also in the phospholipid content and FA composition of both erythrocyte membranes from hypertensive patients and aorta membranes from spontaneously hypertensive rats. 10,11 Moreover, a slight reduction in saturated fat intake along with the use of olive oil markedly lowers the drug requirements of hypertensive patients. 12 Nevertheless, the mechanisms underlying the cardiovascular benefits of this diet are not fully understood.…”
mentioning
confidence: 99%
“…like calcium channel antagonist, closely mimicking the effects of the calcium channel blocker drug verapamil.1 Another suggested mechanism is via improved endothelial function. [35] Oleic acid may contribute to improved endothelial function by reducing ROS. Other potential mechanisms have been suggested, including decreasing vascular tone and changes to the fatty acid and phospholipid composition of the aorta.…”
Section: Hypertensionmentioning
confidence: 99%